OP0294-PARE Addressing key challenges of lay involvement in musculoskeletal research: co-applicants and trial steering committees. (12th June 2018) - Higginbottom, A.; Blackburn, S.; Taylor, R.; Rhodes, C.; Campbell, L.; Dziedzic, K.
Abstract : Background: Patient and Public Involvement (PPI) in research is a requirement of funding in the UK. It has shown to improve the relevance and quality of research. For over 10 years, a Research User Group (RUG) of over 100 patients with musculoskeletal and other long term conditions who actively work with a Research Institute. 1 Researcher and anecdotal feedback from RUG members and researchers have highlighted two challenging PPI roles: lay co-applicants on research grants and lay membership of trial study steering committees (TSCs). For some RUG members, this has resulted in a less positive experience and a disinterest in having these important roles in the future Objectives: To address the challenges of involving RUG members as co-applicants and as members of TSCs, and to describe ways of supporting RUG members in these roles. Methods: Information to improve understanding of the challenges of these roles were gathered during group meetings and informal conversations with 13 RUG members, and a workshop with 35 researchers. PPI and researcher perspectives were captured on flipcharts, notes and meeting minutes. This information shaped the development of resources and approaches to support RUG members as lay co-applicants and TSC members. Results: Conclusions: Providing support to RUG members and researchers can sustain active and long-term lay involvement in these challenging yet important research roles. Reference: [1] Jinks, et al. Res Involv Engagem 2016;2:1. Acknowledgements: We thank all RUG members for their contribution to our research, and R Taylor, C Ingram, C Walker, S Dent, P Callaghan for their input to training and guidance. We thank the Primary Care Consortium and Arthritis Research UK for supporting the RUG. KD is part-funded by a NIHR Knowledge Mobilisation Research Fellowship (KMRF-2014–03–002). Disclosure of Interest: None declared